Structure of Hepatitis C Virus Polymerase in Complex with Primer-Template RNA - Mosley, Ralph T. (American Society for Microbiology, 2012)
The replication of the hepatitis C viral (HCV) genome is accomplished by the NS5B RNA-dependent RNA polymerase (RdRp), for which mechanistic understanding and structure-guided drug design efforts have been hampered by its propensity to crystallize in a closed, polymerization-incompetent state. The removal of an autoinhibitory β-hairpin loop from genotype 2a HCV NS5B increases de novo RNA synthesis by >100-fold, promotes RNA binding, and facilitated the determination of the first crystallographic structures of HCV polymerase in complex with RNA primer-template pairs. These crystal structures demonstrate the structural realignment required for primer-template recognition and elongation, provide new insights into HCV RNA synthesis at the molecular level, and may prove useful in the structure-based design of novel antiviral compounds. Additionally, our approach for obtaining the RNA primer-template-bound structure of HCV polymerase may be generally applicable to solving RNA-bound complexes for other viral RdRps that contain similar regulatory β-hairpin loops, including bovine viral diarrhea virus, dengue virus, and West Nile virus.